‘Crush Programme’ as Part of Combined Control Programme for Culex Mosquito in Both North and South Dhaka City Corporation - Md Nurul Karim, Abul Masud; Afroz, Tamanna; Halim, Kazi Shafiqul; Begum, Masuma; Parvez, Tarique Mehedi (Bangladesh Medical Journal, 2021)
Abstract not available Bangladesh Med J. 2020 Sept; 49(3) : 53-56